PENERAPAN PEMBELAJARAN MEDIA BOOKLET PADA MATERI OPERASI HITUNG BENTUK ALJABAR DI KELAS VII SMP - Noviyanti Maulidia Ningrum; Halini Halini; Ahmad Yani (Universitas Tanjungpura, 2018)
AbstractThis research aimed to know the application in learning using Booklet media on arithmethic operation of algebra in junior high school. The method of this research was experiment and the research design was pre-experiment with one shoot case study. The subject of this research were 34 students of grade 7th A in SMP Negeri 2 Pontianak. The result of this research found that the application in learning using Booklet media on arithmethic operation of algebra in 7th A of SMP Negeri 2 Pontianak was effective in both result posttest and student’s activity. Based on the result of posttest, there were 27 students (82%) that had score more than or equal to 60 points and only 7 students (18%) had score below than 60 points. Based on result of student’s activity, the application in learning using Booklet media on arithmethic operation of algebra in 7th A of SMP Negeri 2 Pontianak was successful to made students learn actively in class, there were 75% students that learn actively in first day and increased to 90% students in second day. Keywords: Intructional media, Booklet, Arithmetic operation in Algebra